(untitled) (Journal of International Studies, 2021)
This article examined the consequences of linking health as a regional security issue. Securitisation Theory (hereinafter ST) is an innovative approach to understand how Non-Traditional Security (from now on NTS) is deemed as a posing threat to a referent object. Prioritising NTS issue as a security threat enables the issue to receive a higher degree of importance from policymakers, thereby gathering the resources needed in dealing with the threat. However, addressing NTS issues also bring negative implications; it can divert attention from more concerning issues. This article, therefore, investigated the consequences of securitising health issues at the Southeast Asian level. This was done through triangulating academic materials, ASEAN’s official statements, and semi-structured elite interviews on Southeast Asian health policy discourses between 1967 and 2010. This study argues that while there are some disadvantages to regional efforts in constructing pandemic disease as a regional security threat, the advantages of such a move outweighs the drawbacks, particularly in terms of establishing regional health mechanisms.